(untitled) (Reflection and Critique Law Magazine, 2020)
The purpose of this article is to analyze the current scenario of the interpretation and application of the rules contained in the Administrative Improbity Law. The differentiation of illegal acts and improper acts will be studied, with a focus on the frequent punitivism that permeates the interpretations / applications of indeterminate concepts and sanctioning rules provided for in the Administrative Improbity Law to justify the scope of the legal types of the improper acts.